Chomsky's Generative Transformational Grammar and its Implications on Language Teaching - DJERIBIAI, Adel (University of Eloued جامعة الوادي, 2016)
The relationship between language and mind has had a considerable interest and research among psychologists and language specialists alike. This relation is often regarded as being intricate due to the nature of language itself and the difficulty of studying the mind as a subject matter. The present contribution attempts to highlight and explain the interrelationship between human language and the mind on the basis of Noam Chomsky's works (namely, 1957,1968) focusing on generative linguistics and innateness. In this respect, this paper sheds light on the implications of Chomsky's cognitive views of language on the teaching / learning of English as a Foreign Language (EFL). It also suggests some pedagogical implications so as to alleviate, if not, eradicate some of the problems encountered by the pedagogical couple (the language teacher and the learner).
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: Language, mind, innateness, EFL. Generative linguistics, Noam Chomsky